2021
DOI: 10.1186/s12929-021-00715-9
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of autophagy by microRNAs in human breast cancer

Abstract: Breast cancer is the most common solid cancer that affects female population globally. MicroRNAs (miRNAs) are short non-coding RNAs that can regulate post-transcriptional modification of multiple downstream genes. Autophagy is a conserved cellular catabolic activity that aims to provide nutrients and degrade un-usable macromolecules in mammalian cells. A number of in vitro, in vivo and clinical studies have reported that some miRNAs could modulate autophagy activity in human breast cancer cells, and these woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…While initially it was thought that autophagy is solely regulated at the protein level, a seminal report in 1999 showed that gene regulatory changes affect autophagy at a transcriptional level [64]. Moreover, autophagy regulation on the post-transcriptional level by non-coding RNAs has also been described, but less studied [65][66][67]. Although the knowledge on autophagy regulation has been expanded significantly, data on post-translational and (post-)transcriptional regulations are scattered across many resources -making it difficult to find and integrate highquality and relevant data.…”
Section: Discussionmentioning
confidence: 99%
“…While initially it was thought that autophagy is solely regulated at the protein level, a seminal report in 1999 showed that gene regulatory changes affect autophagy at a transcriptional level [64]. Moreover, autophagy regulation on the post-transcriptional level by non-coding RNAs has also been described, but less studied [65][66][67]. Although the knowledge on autophagy regulation has been expanded significantly, data on post-translational and (post-)transcriptional regulations are scattered across many resources -making it difficult to find and integrate highquality and relevant data.…”
Section: Discussionmentioning
confidence: 99%
“…While initially it was thought that autophagy is solely regulated at the protein level, a seminal report in 1999 showed that gene regulatory changes affect autophagy at a transcriptional level [ 65 ]. Moreover, autophagy regulation on the post-transcriptional level by non-coding RNAs has also been described, but less studied [ 66 , 67 ]. Although the knowledge on autophagy regulation has been expanded significantly, data on post-translational and (post-)transcriptional regulations are scattered across many resources – making it difficult to find and integrate high-quality and relevant data.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that autophagy is a ‘two‐edged sword’; it inhibits malignant development. In the early stages of cancer, it reduces chromatin instability, tissue damage, and inflammation mostly related to cancer growth (Arun et al, 2015; Chong et al, 2021). Autophagy may perform a complicated role throughout later phases depending on internal and external circumstances.…”
Section: Signaling Pathways In Pathogenesis Of Bcmentioning
confidence: 99%